Association of Caloric Intake, Protein Intake, and Enteral Feeding Initiation with Weight Gain in Infants Born 32 to 34 Weeks' Gestation - Talbo, Meryem Khadija; Besner, Marie-Eve; Plourde, Hugues; Claveau, Martine; Beltempo, Marc (American Journal of Perinatology, 2019)
Objective This study aimed to determine the association of caloric intake, protein intake, and enteral feed initiation time in the first 3 days of life with weight loss percentage (%WL) at 7 days among infants born 32 to 34 weeks' gestational age (GA).Study Design This is a retrospective cohort study of 252 infants admitted to a neonatal intensive care unit. Patient data included patient characteristics, daily weight, intake, and method of nutrition in the first 3 days. Multivariate linear regression was used to explore associations between outcome (%WL at day 7 of life) and exposures (caloric intake, protein intake, and enteral feed initiation time) and adjusted for covariates (GA, birth weight, and sex).Results Median 7 days %WL was 2.3% (interquartile range: −5.2, 1.2). Average caloric intake and average protein intake in the first 3 days were 57 kcal/kg/d and 2.3 g/kg/d. In the adjusted linear regression, caloric intake and protein intake (coefficient = 0.03, 95% confidence interval [CI]: −0.06, 0.09 and coefficient = 0.11, 95% CI: −0.36, 2.30) were not associated with %WL at 7 days. Enteral feeds ≤12 hours were associated with less %WL at 7 days of life (Coef = −0.15, 95% CI: −2.67, −0.17).Conclusion Enteral feeds ≤12 hours after delivery is associated with lower %WL at 7 days among preterm infants 32 to 34 weeks' GA.
Keywords: preterm; nutrition; growth; parenteral nutrition; enteral nutrition